Analisis Pengaruh Lingkungan Pembelajaran Virtual Terhadap Motivasi Belajar Mahasiswa Ekonomi Syariah UIN Sultan Maulana Hasanuddin Banten - Syahlaa Salsabiil Putri; Fitri Rohimah; Muslihah Muslihah; Mukhlishotul Jannah; Wahyu Hidayat; Fitri Fitri (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Education is a process in which educators and students work together to create benefits, skilled attitudes, and personalities. In the midst of the pandemic, the government is encouraging educational institutions to change students from face-to-face learning to virtual, or distance, learning. Virtual learning remains another option when teachers cannot be in class. This research aims to understand how the learning environment influences the desire to learn. This study uses a quantitative approach. A sample of 30 sharia economics study program students at UIN Sultan Maulana Hasanuddin Banten received a questionnaire via Google form. Data were then collected using the SPSS Version 25 program. This research found that the online learning environment influenced students' desire to study sharia economics at UIN Sultan Maulana Hasanuddin Banten. The findings show that some students experience difficulties in learning the lessons given by their teachers during online learning, which results in a decrease in their desire to learn. Therefore, to increase student motivation and learning outcomes, the quality of learning on campus must be improved.